(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Grain quality is a complex character that depends on a number of traits, and the individual contribution of each trait varies depending on specific reaction to environmental conditions. The objective of this study was to assess the effects of genotype, environmental, and genotype x environmental interaction on quality characteristic of 16 wheat genotypes as well as to analyse the relationships between quality traits. The results of two-way analysis of variance showed that the effect of genotype, environment and genotype x environment interaction were significant (p≤0.001) for the investigated physical characteristics of grain. The strongest individual influence for thousand kernel weight, test weight and vitreousness had genotype. The interaction genotype x environment had stronger influence on the variance for the crude protein (44.98%) and the lysine (34.93%) than genotype and environment effects. Sources of variation genotype and genotype x environment interaction (year) had almost the equal influence on the variance of wet gluten content and bread making strength index. Genotype demonstrated the strongest influence on the sedimentation value and dry gluten content. The genotype x environment interaction influenced in the largest rate on the variance of gluten weakness. Protein content showed significant positive correlation with wet gluten content (0.676), gluten weakness (0.646) and dry gluten content. Vitreousness correlated positively with sedimentation value (0.541) while the test weight significantly correlated with dry gluten content. The results of this study can be used as selection criteria to increase grain quality in bread wheat in the region.